Postsocialist Landscapes real and imaginary spaces from Stalinstadt to Pyongyang - Lahusen, Thomas; Schahadat, Schamma (Bielefeld : transcript, 2020)
Since the fall of the Iron Curtain, formerly socialist countries have gone through manifold transformations, whilst remnants of socialism remain ubiquitous. The volume explores various spaces of the postsocialist landscape, presenting a mixture of real and imaginary spaces, of memory and nostalgia, of aesthetic and political symbolism, of the global East and the global South, of academic and essayistic writing. It casts a glance at the heterogeneous relics of socialism and their transformation in very different parts of the world. From the description of (post-)socialist interiors, façades, neighborhoods, parks, monuments, and objects towards the imaginary spaces of literature, the contributors describe the concreteness and intimacy of some of the places that span across and even beyond of what is left of the "second world" today
Literaturangaben
Keywords: Postkommunismus; Aufsatzsammlung